Three Cases of Hemiconvulsion-Hemiplegia-Epilepsy Syndrome With Focal Cortical Dysplasia Type IIId - Itamura, Shinji; Okanishi, Tohru; Arai, Yoshifumi; Nishimura, Mitsuyo; Baba, Shimpei; Ichikawa, Naoki; Hirayama, Yoshimichi; Ishihara, Naoko; Hiraide, Takuya; Ishigaki, Hidetoshi; Fukuda, Tokiko; Otsuki, Yoshiro; et al. (Frontiers in Neurology, 2019)
Hemiconvulsion-hemiplegia-epilepsy syndrome (HHES) is a subset of acute encephalopathy characterized by infantile-onset with acute hemiconvulsive febrile status and subsequent unilateral cerebral atrophy and hemiparesis. In the chronic phase, patients with HHES develop epilepsy, typically displayed as intractable focal seizures. The patients are often intractable with antiepileptic drugs and need surgical treatment. Although viral encephalitis and genetic abnormalities are presumed to be the underlying etiology, the pathogenesis remains mostly unknown. We describe three cases of successful functional hemispherotomy for intractable epilepsy in HHES. Patients developed acute asymmetrical convulsive status following viral infections during the ages of 17 to 30 months. Their seizures were intractable with antiepileptic drugs and required hemispherotomy. On the basis of the pathological findings, all cases were diagnosed as focal cortical dysplasia type IIId. The epileptogenic mild cortical malformations may be the cause of HHES.